2010
DOI: 10.1016/j.devcel.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome-Depleted Regions in Cell-Cycle-Regulated Promoters Ensure Reliable Gene Expression in Every Cell Cycle

Abstract: Summary Many promoters in eukaryotes have nucleosome depleted regions (NDR) containing transcription factor binding sites (TFBS). However, the functional significance of NDR is not well understood. Here, we examine NDR function in two cell-cycle-regulated promoters, CLN2pr and HOpr, by varying nucleosomal coverage of the binding sites of their activator SBF (SCBs) and probing the corresponding transcriptional activity in individual cells using time-lapse microscopy. Nucleosome-embedded SCBs do not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 73 publications
(112 reference statements)
3
84
0
4
Order By: Relevance
“…Similar to the effect of TATA-boxes, the increase in expression variability observed with two NF-Y sites or with a higheraffinity site was mediated primarily by an increase in the average burst size, whereas the burst frequency was largely unaffected (Suter et al 2011). Chromatin regulation has also been linked to expression variability (Blake et al 2003;Raser and O'Shea 2004;Field et al 2008;Choi and Kim 2009;Bai et al 2010), with two studies showing that adding nucleosome-disfavoring sequences to a yeast promoter resulted in lower nucleosome occupancy and reduced expression variability (Bai et al 2010;Raveh-Sadka et al 2012). However, in contrast to the effect of TATA-boxes and TF sites, chromatin was suggested to mainly affect the frequency with which promoters transition between transcriptionally active and inactive states (Raser and O'Shea 2004).…”
mentioning
confidence: 69%
“…Similar to the effect of TATA-boxes, the increase in expression variability observed with two NF-Y sites or with a higheraffinity site was mediated primarily by an increase in the average burst size, whereas the burst frequency was largely unaffected (Suter et al 2011). Chromatin regulation has also been linked to expression variability (Blake et al 2003;Raser and O'Shea 2004;Field et al 2008;Choi and Kim 2009;Bai et al 2010), with two studies showing that adding nucleosome-disfavoring sequences to a yeast promoter resulted in lower nucleosome occupancy and reduced expression variability (Bai et al 2010;Raveh-Sadka et al 2012). However, in contrast to the effect of TATA-boxes and TF sites, chromatin was suggested to mainly affect the frequency with which promoters transition between transcriptionally active and inactive states (Raser and O'Shea 2004).…”
mentioning
confidence: 69%
“…Using a cell cycle-regulated CLN2 promoter (CLN2pr) as a model, we found that a nucleosomedepleted region (NDR) over the activator SBF (Swi4/6) binding sites ensures reliable gene expression (4). In particular, when the SBF binding sites on CLN2pr are nucleosome-embedded, they induce "on/off" activation in individual cell cycles.…”
mentioning
confidence: 99%
“…Dans une étude récente [11], nous avons apporté un éclairage nouveau sur ces questions. Dans la plupart des études précédentes, les données transcriptionnelles étaient exprimées comme la moyenne de mesures faites dans des populations de cellules.…”
Section: Présence De Nucléosomes Et Activation De La Transcriptionunclassified
“…Quelques éléments de réponse peuvent être tirés de notre étude ainsi que d'autres travaux empruntés à la littérature. En premier lieu, l'activation à partir d'un site de fixation nucléo somal peut requé-rir une concentration plus élevée d'activateurs et dépendre davantage des complexes de remodelage de la chromatine [7][8][9][10][11]. Le coût lié à ces deux processus pourrait être bien supérieur à celui nécessaire à la déplétion de quelques nucléosomes.…”
Section: Présence De Nucléosomes Et Activation De La Transcriptionunclassified